Healthy Cookies: Nutritious Food Innovation Through Fortification By-products of Tuna (Thunnus sp.) Fish Bone Flour - Gressty Sari Br Sitepu; Safira Noor Andayani; Gede Iwan Setiabudi; Made Dwipa Kusuma Maharani; Fenny Crista Anastasia Panjaitan (Advances in Tropical Biodiversity and Environmental Sciences, 2023)
Healthy cookies is one of the processed pastries by utilizing the nutritional content contained in tuna fish bone by-products so that it is used as an alternative snack for people with osteoporosis. This study aims to analyze the chemical and sensory characteristics of cookies added with tuna fish bone flour. The research method used was an experimental method with two treatments, namely cookies without the addition of tuna fish bone flour and cookies with 6% tuna fish bone flour substitution which were analyzed using one-way Anova on XLStat software. The results showed that the addition of 6% tuna fish bone flour produced higher values of ash, protein and fat content, namely 3.170%, 25.878% and 43.865% while the water content and carbohydrates decreased, namely 5.488% and 21.599% The sensory results of cookies adding tuna fish bone flour received a "good" assessment of color and texture and "neutral" on aroma, taste and overall acceptability.